Burnout in Orthopaedic Surgeons: A Challenge for Leaders, Learners, and Colleagues. (19th July 2017) - Ames, S. Elizabeth; Cowan, James B.; Kenter, Keith; Emery, Sanford; Halsey, David
Abstract : Abstract: Burnout, depression, suicidal ideation, and dissatisfaction with work-life balance have been reported in all medical specialties and at all stages of medical education and practice experience. Burnout consists of progressive emotional, attitudinal, and physical exhaustion. Physicians with burnout may treat patients as objects and feel emotionally depleted. Burnout is characterized by a loss of enthusiasm for work (emotional exhaustion), feelings of cynicism (depersonalization), and a low sense of personal accomplishment. The most complete study of emotional burnout among different medical specialties demonstrated that orthopaedic surgery is one of the specialties with the highest burnout rate. Qualitative descriptive studies are available. There was a 45.8% burnout rate among physicians in the U.S. in 2012, and a 2014 update suggested even higher rates. Burnout has a correlation with medical education. Burnout rates are similar to those in the general population when medical students enter school, and increase steadily through medical education prior to residency. Burnout rates in residents are high, reported to be between 41% and 74% across multiple specialties. This impacts our young physician workforce in orthopaedics. The purpose of this review is to provide the available information that characterizes burnout and addresses the issues inherent to preventing burnout, and to build awareness in orthopaedic surgeons. Wellness "goes beyond merely the absence of distress and includes being challenged, thriving, and achieving success in various aspects of personal and professional life." The challenge for the orthopaedic community is to develop interventions and strategies that are personalized to the individuals in this specialty.